Curing agent, two-component paint, coating and application of two-component paint and coating

By using a curing agent composed of phenoamine curing agent, a diethylenetriamine and a hydroxymethylurea compound, a coating with excellent acid corrosion resistance is formed, which solves the problem of short service life of existing coatings in strong acid environments and achieves effective resistance to a variety of acid corrosion media.

CN119684574AActive Publication Date: 2025-03-25SHUANGRUN NEW MATERIAL TECH (NANJING) CO LTD

Patent Information

Application Number
CN202411856943.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-17
Publication Date
2025-03-25
Estimated Expiration
2044-12-17

AI Technical Summary

Technical Problem

The existing corrosion-resistant coatings have a short service life in strong acid corrosion environments and have insufficient acid corrosion resistance, making it difficult to effectively solve the problem of acid corrosion in the oil and natural gas refining industry.

Method used

A curing agent composed of a phenoamine curing agent, a diethylenetriamine and a hydroxymethylurea compound is used as a curing agent for an epoxy resin to form a coating with excellent acid corrosion resistance.

Benefits of technology

The curing agent introduces the self-polymerization reaction of hydroxymethylurea compounds into the coating, effectively preventing the corrosion of hydrogen ions and filling the coating voids, significantly improving the acid corrosion resistance of the coating and resisting the corrosion of organic acids, hydrochloric acid, sulfuric acid and hydrofluoric acid.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119684574A_ABST
    Figure CN119684574A_ABST
Patent Text Reader

Abstract

The invention provides a curing agent, a two-component coating, a coating and application of the two-component coating and the coating, and belongs to the technical field of heavy anti-corrosion coatings. The curing agent provided by the invention is prepared from the following raw materials in parts by mass: 60-85 parts of a phenolic aldehyde amine curing agent, 5-20 parts of diethylenetriamine and 5-20 parts of a hydroxymethyl urea compound. The hydroxymethylurea compound is introduced into the curing agent, and carbonyl of the hydroxymethylurea compound has a strong electron withdrawing effect, so that adjacent secondary amino groups hardly participate in an epoxy curing reaction at room temperature; hydrogen on a secondary amine group in the introduced hydroxymethyl urea compound and hydroxymethyl of the hydroxymethyl urea compound are subjected to a dehydration self-polymerization reaction to form a macromolecular product, so that erosion of hydrogen ions is effectively prevented, internal gaps of the coating are filled, further corrosion of water, the hydrogen ions and salt to the coating is prevented, and the purpose of resisting acid corrosion is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of heavy-duty anticorrosive coatings, and in particular relates to a curing agent, a two-component coating and a coating and applications thereof. Background Art

[0002] As an important chemical raw material, petroleum and natural gas play an important role in the development of the national economy. The related oil refining industry has been facing the situation of increasing high-sulfur crude oil and heavy crude oil, which brings a series of corrosion problems, seriously affecting the service life of equipment, especially in the sulfur chemical industry downstream of crude oil processing, where corrosion is mainly acid corrosion. To solve the acid corrosion problem, the industry mainly uses acid corrosion resistant coatings, which can be applied by brushing or spraying, have good surface forming and low cost.

[0003] The anti-corrosion coatings currently used in the industry are mainly: vinyl glass flake coatings, epoxy zinc-rich coatings and polyurethane coatings, but these coatings still have poor corrosion resistance, especially in strong acid corrosion environments, and have a short service life. Therefore, how to improve the acid corrosion resistance of coatings has become a technical problem that needs to be solved urgently in this field. Summary of the invention

[0004] The purpose of the present invention is to provide a curing agent, a two-component paint and a coating and their application. The curing agent provided by the present invention, when used as a curing agent for epoxy resin, enables the coating to have excellent acid corrosion resistance.

[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0006] The present invention provides a curing agent, which is prepared from the following raw materials in parts by weight:

[0007] 60-85 parts of phenalkamine curing agent,

[0008] 5 to 20 parts of diethylenetriamine,

[0009] and 5 to 20 parts of hydroxymethyl urea compounds.

[0010] Preferably, the methylol urea compound includes at least one of monomethylol urea, dimethylol urea and trimethylol urea.

[0011] Preferably, the preparation method of the phenalkamine curing agent comprises: mixing long-chain phenol, paraformaldehyde, polyamine and solvent, and performing polymerization reaction to obtain the phenalkamine curing agent;

[0012] The chain length of the long-chain phenol is at least one of C7 to C15.

[0013] Preferably, the long-chain phenol includes at least one of cardanol, heptylphenol, octylphenol, nonylphenol and decylphenol.

[0014] The present invention also provides a two-component coating, the raw materials of which include material A and material B;

[0015] The material A is prepared from the following raw materials in parts by weight:

[0016]

[0017] The material B is the curing agent described in the above technical solution;

[0018] The ratio of the epoxy equivalent of the material A to the active hydrogen equivalent of the material B excluding the hydroxymethyl urea compound is (0.9-1.1): (0.9-1.1).

[0019] Preferably, the multifunctional epoxy resin includes at least one of novolac epoxy resin, resorcinol formaldehyde epoxy resin, tetraphenol ethane tetraglycidyl ether and tetraglycidyl diaminodiphenylmethane.

[0020] Preferably, the epoxy reactive diluent comprises at least one of aliphatic glycidyl ether and aromatic glycidyl ether.

[0021] Preferably, the barrier filler includes at least one of glass flake powder, lamellar boron nitride and mica powder.

[0022] The present invention also provides a coating, the coating is composed of the two-component coating described in the above technical solution.

[0023] The present invention also provides the use of the two-component coating described in the above technical solution or the coating described in the above technical solution in acid corrosion resistance.

[0024] The present invention provides a curing agent, which is prepared from the following raw materials in parts by weight: 60 to 85 parts of phenolic amine curing agent, 5 to 20 parts of diethylenetriamine and 5 to 20 parts of hydroxymethyl urea compounds. The present invention introduces hydroxymethyl urea compounds into the curing agent, and its carbonyl group has a strong electron-withdrawing effect, resulting in the adjacent secondary amine group hardly participating in the epoxy curing reaction at room temperature. When hydrogen ions penetrate into the interior of the coating in the immersion environment, the active hydrogen on the secondary amine group in the introduced hydroxymethyl urea compound will undergo a self-polymerization reaction with the self-carried hydroxymethyl, effectively preventing the corrosion of hydrogen ions, while filling the internal gaps of the coating, preventing water, hydrogen ions, and salts from further corroding the coating, thereby achieving the purpose of acid corrosion resistance. Experimental results show that the coating prepared using the curing agent provided by the present invention can effectively resist the corrosion of organic acids, 37wt% hydrochloric acid, 98wt% sulfuric acid and 40wt% hydrofluoric acid, and has a wide range of effects on resisting organic acids and inorganic acids. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1The weight loss curve of the cylinder prepared by the two-component coating of Application Examples 1 to 2 and Application Example 1 when it is immersed in 99wt% glacial acetic acid;

[0026] Figure 2 This is a macroscopic image of a cylinder prepared by using the two-component coating of Application Example 1;

[0027] Figure 3 This is a macroscopic image of a cylinder prepared by the two-component coating of Application Example 1 and immersed in 37 wt % hydrochloric acid for 7 days;

[0028] Figure 4 This is a macroscopic image of a cylinder prepared by the two-component coating of Application Example 1 and immersed in 98wt% sulfuric acid for 7 days;

[0029] Figure 5 This is a macroscopic image of a cylinder prepared with the two-component coating of Application Example 1 and immersed in 40 wt % hydrofluoric acid for 7 days. DETAILED DESCRIPTION

[0030] The present invention provides a curing agent, which is prepared from the following raw materials in parts by weight:

[0031] 60-85 parts of phenalkamine curing agent,

[0032] 5 to 20 parts of diethylenetriamine,

[0033] and 5 to 20 parts of hydroxymethyl urea compounds.

[0034] The present invention has no particular limitation on the sources of the raw materials, and commercially available products known to those skilled in the art may be used.

[0035] The raw materials for preparing the curing agent of the present invention include 60 to 85 parts of phenalkamine curing agent by weight. In the present invention, the phenalkamine curing agent can make the prepared coating have a high overall crosslinking density and excellent acid corrosion resistance.

[0036] As an embodiment, the phenalkamine curing agent may be 65 to 80 parts, or 70 to 78 parts.

[0037] In the present invention, the active hydrogen equivalent of the phenalkamine curing agent is preferably 137 to 151 g / mol.

[0038] In the present invention, the preparation method of the phenalkamine curing agent preferably comprises: mixing long-chain phenol, paraformaldehyde and polyamine, and performing polymerization reaction to obtain the phenalkamine curing agent.

[0039] In the present invention, the chain length of the long-chain phenol is preferably at least one of C7 to C15; the long-chain phenol preferably includes at least one of cardanol, heptylphenol, octylphenol, nonylphenol and decylphenol; the polyamine preferably includes at least one of ethylenediamine, hexamethylenediamine, diethylenetriamine, p-xylenediamine, p-phenylenediamine, diaminodiphenylmethane, triethylenetetramine and diaminodiphenyl. In the present invention, the phenalkamine curing agent is prepared using long-chain phenol. The longer alkane chain in the long-chain phenol can improve the hydrophobicity of the coating, effectively preventing corrosive ions from penetrating into the coating with water, thereby improving its acid corrosion resistance.

[0040] When the long-chain phenols are of multiple types, the present invention has no particular limitation on the ratio of the multiple types of long-chain phenols, and the ratio can be set as required.

[0041] When the polyamine is of multiple types, the present invention has no particular limitation on the ratio of the multiple polyamines, and the ratio can be set as required.

[0042] In the present invention, the molar ratio of the long-chain phenol, polyformaldehyde and polyamine is preferably 1:(1-1.05):(1.2-1.4). As an embodiment, the molar ratio of the long-chain phenol, polyformaldehyde and polyamine can be 1:1:(1.2-1.3).

[0043] The present invention has no special limitation on the operation of mixing the long-chain phenol, paraformaldehyde and polyamine, and the operation well known to those skilled in the art can be adopted.

[0044] In the present invention, the polymerization reaction temperature is preferably 85-120° C., and the polymerization reaction time is preferably 2-5 hours. As an embodiment, the polymerization reaction temperature may be 90-95° C., and the polymerization reaction time may be 3-4 hours.

[0045] After the polymerization reaction is completed, the present invention preferably subjects the product obtained by the polymerization reaction to a decompression treatment to obtain a phenalkamine curing agent.

[0046] The present invention has no particular limitation on the operation of the decompression treatment, and water can be removed by using an operation well known to those skilled in the art.

[0047] As an embodiment, the preparation method of the phenolic amine curing agent can be: take 30.25 parts by mass of cardanol and 22.03 parts by mass of nonylphenol, stir and mix, add 29.25 parts by mass of triethylenetetramine, 11.6 parts by mass of hexamethylenediamine, and 19.8 parts by mass of diaminodiphenylmethane, stir at 300 rpm and heat to 80°C, add 6 parts by mass of paraformaldehyde three times, 2 parts by mass each time, each time with an interval of 20 minutes, continue to keep warm for 30 minutes, heat to 120°C for polymerization reaction for 3 hours, and decompress and dehydrate to obtain the phenolic amine curing agent.

[0048] Based on 60 to 85 parts by mass of the phenalkamine curing agent, the raw materials for preparing the curing agent of the present invention also include 5 to 20 parts of diethylenetriamine. As an embodiment, the diethylenetriamine can be 10 to 15 parts, or 11.5 to 13 parts. In the present invention, the diethylenetriamine can reduce the overall viscosity of the curing agent, and the lower molecular weight can also increase the crosslinking density of the coating, thereby improving the chemical resistance and acid corrosion resistance of the coating.

[0049] Based on 60 to 85 parts by mass of the phenolic amine curing agent, the raw materials for preparing the curing agent of the present invention also include 5 to 20 parts of methylol urea compounds; the methylol urea compounds preferably include at least one of monomethylol urea, dimethylol urea and trimethylol urea, more preferably dimethylol urea; the dimethylol urea preferably includes 1,3-bismethylol urea. In the present invention, the methylol urea compounds utilize the characteristics of self-polymerization under acidic conditions to further improve the crosslinking density of the coating under acidic conditions and fill the gaps in the coating, closing the invasion channels of hydrogen ions, etc., thereby achieving a long-term acid corrosion resistance effect; when the methylol urea compound is dimethylol urea, the strong electron-withdrawing effect of its carbonyl group is utilized, and the reaction activity with the epoxy group in the coating is low. Under room temperature curing conditions, the epoxy group is basically not consumed, and the crosslinking density of the coating is ensured while maintaining its own structure.

[0050] As an embodiment, the hydroxymethyl urea compound may be 8 to 17.5 parts, or may be 10 to 15 parts.

[0051] Based on 60 to 85 parts by mass of the phenolic amine curing agent, the raw materials for preparing the curing agent of the present invention preferably also include 0.5 to 3 parts of fumed silica; the particle size of the fumed silica is preferably 7 to 40 nm. In the present invention, the fumed silica mainly plays the role of anti-settling and suspension, which can increase the viscosity of the coating and prevent the barrier filler in the coating from settling.

[0052] As an implementation mode, the fumed silica may be 1 to 2 parts.

[0053] In the present invention, the preparation method of the curing agent is preferably:

[0054] The phenalkamine curing agent, diethylenetriamine and hydroxymethyl urea compound are mixed to obtain material B.

[0055] In the present invention, the mixing of the phenalkamine curing agent, diethylenetriamine and hydroxymethyl urea compound is preferably carried out under stirring; the stirring speed is preferably 800 to 1500 rpm; and the stirring time is preferably 20 to 30 min.

[0056] As an implementation manner, the stirring speed may be 1000-1200 rpm; the stirring time may be 22-26 min.

[0057] In the present invention, when the material B includes fumed silica, it is preferably added before mixing.

[0058] The present invention introduces hydroxymethyl urea compounds into the curing agent, and the carbonyl groups of the hydroxymethyl urea compounds have a strong electron-withdrawing effect, so that the adjacent secondary amine groups hardly participate in the epoxy curing reaction at room temperature. When hydrogen ions penetrate into the interior of the coating in an immersion environment, the hydrogen on the secondary amine groups of the introduced hydroxymethyl urea compounds will undergo a self-polymerization reaction with the hydroxymethyl groups of the hydroxymethyl urea compounds, effectively preventing the corrosion of hydrogen ions, and filling the internal gaps of the coating, thereby preventing water, hydrogen ions and salts from further corroding the coating, thereby achieving the purpose of long-term acid corrosion resistance.

[0059] The present invention provides a two-component coating, the raw materials of which include material A and material B;

[0060] The material A is prepared from the following raw materials in parts by weight:

[0061] 30-45 parts of multifunctional epoxy resin,

[0062] Epoxy reactive diluent 5-15 parts,

[0063] Barrier filler 20-60 parts,

[0064] 10-30 parts of glass powder,

[0065] and 0.3 to 1 part of coupling agent;

[0066] The material B is the curing agent described in the above technical solution;

[0067] The ratio of the epoxy equivalent of the material A to the active hydrogen equivalent of the material B excluding the hydroxymethyl urea compound is (0.9-1.1): (0.9-1.1).

[0068] The present invention has no particular limitation on the sources of the raw materials, and commercially available products known to those skilled in the art may be used.

[0069] In the present invention, the raw materials for preparing the two-component coating include material A. In the present invention, the material A is a resin component.

[0070] In the present invention, the raw materials for preparing the material A include 30 to 45 parts by mass of a multifunctional epoxy resin; the multifunctional epoxy resin preferably includes at least one of a phenolic epoxy resin, a resorcinol formaldehyde epoxy resin, tetraphenol ethane tetraglycidyl ether and tetraglycidyl diaminodiphenylmethane; the phenolic epoxy resin is preferably an o-cresol epoxy resin. In the present invention, the multifunctional epoxy resin can be cross-linked and cured with the phenolic amine curing agent and diethylenetriamine in the material B at room temperature, thereby increasing the cross-linking density of the coating and further improving the acid corrosion resistance.

[0071] As an implementation manner, the multifunctional epoxy resin may be 32 to 43 parts, or 35 to 38 parts.

[0072] Based on the mass fraction of the multifunctional epoxy resin being 30 to 45 parts, the raw materials for preparing the material A also include 5 to 15 parts of epoxy reactive diluent; the epoxy reactive diluent is preferably at least one of aliphatic glycidyl ether and aromatic glycidyl ether; the aliphatic glycidyl ether preferably includes at least one of 1,4-butanediol diglycidyl ether, glycerol triglycidyl ether and trimethylolpropane triglycidyl ether; the aromatic glycidyl ether preferably includes at least one of phenyl glycidyl ether and resorcinol diglycidyl ether. In the present invention, the epoxy reactive diluent will participate in the curing reaction of the epoxy resin, become part of the cross-linked network structure of the epoxy resin cured product, maintain the integrity of the coating, and thus improve the acid corrosion resistance.

[0073] As an embodiment, the epoxy reactive diluent may be 6 to 12 parts, or 8 to 10 parts.

[0074] Based on the mass fraction of the multifunctional epoxy resin being 30 to 45 parts, the raw materials for preparing the material A also include 20 to 60 parts of barrier fillers; the barrier fillers preferably include at least one of glass flakes, lamellar boron nitride and mica powder; the size of the barrier fillers is preferably 30 to 60 μm. In the present invention, the barrier fillers play a barrier role, thereby slowing down the erosion rate of water, hydrogen ions, salts, etc. on the coating; the addition of lamellar boron nitride, a lamellar filler, can form a "maze" effect in the coating, greatly slowing down the erosion rate of water, hydrogen ions, salts, etc. on the coating.

[0075] As an implementation manner, the barrier filler may be 25 to 50 parts, or may be 31 to 40 parts.

[0076] Based on 30 to 45 parts by mass of the multifunctional epoxy resin, the raw materials for preparing the material A also include 10 to 30 parts of glass powder; the particle size of the glass powder is preferably 30 to 50 μm. In the present invention, the glass powder has strong chemical stability and does not react with most chemical substances, so that the coating can remain stable in various chemical environments, thereby improving the acid corrosion resistance.

[0077] As an implementation manner, the glass powder may be 15 to 25 parts, or 18 to 20 parts.

[0078] Based on 30 to 45 parts by mass of the multifunctional epoxy resin, the raw materials for preparing the material A also include 0.3 to 1 part of a coupling agent; the coupling agent preferably includes at least one of a silane coupling agent, a titanate coupling agent and an aluminate coupling agent, and more preferably a KH-560 coupling agent. In the present invention, the coupling agent can improve the dispersibility of inorganic substances such as barrier fillers and glass powder in the multifunctional epoxy resin.

[0079] As an embodiment, the coupling agent may be 0.5 to 0.8 parts, or 0.6 to 0.7 parts.

[0080] Based on 30 to 45 parts by mass of the multifunctional epoxy resin, the raw materials for preparing the material A preferably also include 0.5 to 3 parts of fumed silica; the particle size of the fumed silica is preferably 7 to 40 nm. In the present invention, the fumed silica mainly plays an anti-settling role, which can enhance the viscosity of the system and prevent the sedimentation of the barrier filler in the coating.

[0081] As an implementation mode, the fumed silica may be 1 to 2 parts.

[0082] In the present invention, the preparation method of material A preferably comprises the following steps:

[0083] (1) mixing a multifunctional epoxy resin, an epoxy reactive diluent and a coupling agent to obtain a mixture;

[0084] (2) The mixed material obtained in step (1), the barrier filler and the glass powder are mixed to obtain material A.

[0085] The present invention preferably mixes a multifunctional epoxy resin, an epoxy reactive diluent and a coupling agent to obtain a mixture.

[0086] In the present invention, the multifunctional epoxy resin is preferably preheated before use; the preheating temperature is preferably 50-70° C., more preferably 60° C. In the present invention, preheating the multifunctional epoxy resin in advance can significantly improve the resin mixing efficiency.

[0087] In the present invention, the mixing of the multifunctional epoxy resin, epoxy reactive diluent and coupling agent is preferably carried out under stirring; the stirring speed is preferably 500-1000 rpm, more preferably 800 rpm; and the stirring time is preferably 5-15 min.

[0088] After obtaining the mixed material, the present invention preferably mixes the mixed material, barrier filler and glass powder to obtain material A.

[0089] In the present invention, the mixing of the mixed material, the barrier filler and the glass powder is preferably carried out under stirring and vacuum degassing conditions in sequence.

[0090] In the present invention, the stirring speed is preferably 800-1000 rpm, more preferably 900 rpm; the stirring time is preferably 20-30 min, more preferably 25 min. The present invention adopts stirring to make the raw materials mixed more uniformly.

[0091] In the present invention, the pressure of the vacuum degassing is preferably 0.01 to 0.02 MPa; the time of the vacuum degassing is preferably 5 to 20 minutes. The vacuum degassing of the present invention can remove gas from the raw material.

[0092] In the present invention, when the material A includes fumed silica, it is preferred that the fumed silica is mixed with the mixed material before the barrier filler and the glass powder are added.

[0093] In the present invention, the mixing of the fumed silica and the mixed material is preferably carried out under stirring conditions; the stirring speed is preferably 100 to 200 rpm; the stirring time is preferably 3 to 10 minutes, more preferably 8 minutes.

[0094] In the present invention, the raw materials for preparing the coating of the present invention further include material B. In the present invention, the material B is a curing agent component.

[0095] In the present invention, the ratio of the epoxy equivalent of the material A to the active hydrogen equivalent of the material B excluding the hydroxymethyl urea compound is (0.9-1.1):(0.9-1.1), preferably 1:1.

[0096] The multifunctional epoxy resin and phenolic amine curing agent in the two-component coating provided by the present invention will make the overall cross-linking density of the coating prepared by the two-component coating high and have excellent acid corrosion resistance; the two-component coating provided by the present invention has the advantages of good heat resistance, strong acid corrosion resistance, resistance to cold and heat shock, etc., is particularly suitable for anti-corrosion use in the petrochemical pipeline industry, can be used for large-area spraying, and has the advantages of wide product application and convenient construction.

[0097] The present invention has no special limitation on the preparation method of the two-component coating, as long as material A and material B are mixed completely.

[0098] The present invention also provides a coating, the coating is composed of the two-component coating described in the above technical solution.

[0099] The coating provided by the invention has excellent acid corrosion resistance.

[0100] The present invention also provides the use of the two-component coating described in the above technical solution or the coating described in the above technical solution in acid corrosion resistance.

[0101] The present invention has no special limitation on the application operation of the two-component paint or coating in acid corrosion resistance, and the application operation familiar to those skilled in the art can be adopted.

[0102] The technical solutions in the present invention will be described clearly and completely below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0103] The preparation methods of the phenalkamine curing agents used in the examples and comparative examples are:

[0104] Take 30.25 parts by mass of cardanol and 22.03 parts by mass of nonylphenol, stir and mix, add 29.25 parts by mass of triethylenetetramine, 11.6 parts by mass of hexamethylenediamine, and 19.8 parts by mass of diaminodiphenylmethane, stir at 300 rpm and heat to 80°C, add 6 parts by mass of paraformaldehyde three times, wherein 2 parts by mass are added each time, each time with an interval of 20 minutes, continue to keep warm for 30 minutes, heat to 120°C for polymerization reaction for 3 hours, and reduce the pressure to remove water to obtain a phenolic amine curing agent with an active hydrogen equivalent of 140 g / mol.

[0105] Example 1

[0106] The curing agent is prepared from the following raw materials in parts by weight:

[0107] 70 parts of phenalkamine curing agent,

[0108] 11.5 parts of diethylenetriamine,

[0109] 17.5 parts of hydroxymethyl urea compounds,

[0110] and 1 part of fumed silica;

[0111] The hydroxymethyl urea compound is 1,3-bishydroxymethyl urea;

[0112] The particle size of the fumed silica is 7 to 40 nm;

[0113] The preparation method of the curing agent is:

[0114] A phenolic amine curing agent, diethylenetriamine, a hydroxymethyl urea compound and fumed silica were weighed and mixed at 1000 rpm for 30 minutes to obtain a curing agent with an active hydrogen equivalent of 95.2 g / mol.

[0115] Application Example 1

[0116] The raw materials of two-component coatings are composed of material A and material B;

[0117] The A material is prepared from the following raw materials in parts by weight:

[0118]

[0119] The multifunctional epoxy resin is Olin DER-440 epoxy resin and Huntsman EPN-1180 epoxy resin in a mass ratio of 17:21;

[0120] The epoxy reactive diluent is trimethylolpropane triglycidyl ether;

[0121] The barrier filler is glass flakes with a size of 30 to 60 μm;

[0122] The particle size of glass powder is 30-50 μm, which is titanium powder;

[0123] The coupling agent is KH-560 coupling agent;

[0124] The particle size of fumed silica is 7 to 40 nm;

[0125] The material B is the curing agent prepared in Example 1;

[0126] The ratio of the epoxy equivalent of the A material to the active hydrogen equivalent of the B material excluding the hydroxymethyl urea compound is 1:1

[0127] The preparation method of the two-component coating comprises the following steps:

[0128] (1) Pour the Olin DER-440 epoxy resin and Huntsman EPN-1180 epoxy resin preheated to 60° C. into a double planetary high-speed disperser, add trimethylolpropane triglycidyl ether and KH-560 coupling agent, mix at 600 rpm for 10 min, continue to add fumed silica, knead at 200 rpm for 10 min, continue to add glass flakes and glass powder, mix at 800 rpm for 25 min, and then vacuum degas at 0.01 MPa for 10 min to obtain material A with an epoxy equivalent of 304.6 g / mol;

[0129] (2) Mix material A and material B in a mass ratio of 3.2:1 to obtain a two-component coating.

[0130] Example 2

[0131] The curing agent is prepared from the following raw materials in parts by weight:

[0132] 78 parts of phenalkamine curing agent,

[0133] 13 parts of diethylenetriamine,

[0134] 8 parts of hydroxymethyl urea compounds,

[0135] and 1 part of fumed silica;

[0136] The hydroxymethyl urea compound is 1,3-bishydroxymethyl urea;

[0137] The particle size of the fumed silica is 7 to 40 nm;

[0138] The preparation method of the curing agent is:

[0139] A phenolic amine curing agent, diethylenetriamine, a hydroxymethyl urea compound and fumed silica were weighed and mixed at 1000 rpm for 30 minutes to obtain a curing agent with an active hydrogen equivalent of 84.8 g / mol.

[0140] Application Example 2

[0141] The raw materials of two-component coatings are composed of material A and material B;

[0142] The A material is prepared from the following raw materials in parts by weight:

[0143]

[0144] The multifunctional epoxy resin is Olin DER-440 epoxy resin and Huntsman EPN-1180 epoxy resin in a mass ratio of 17:21;

[0145] The epoxy reactive diluent is trimethylolpropane triglycidyl ether;

[0146] The barrier filler is glass flakes with a size of 30 to 60 μm;

[0147] The particle size of glass powder is 30-50 μm, which is titanium powder;

[0148] The coupling agent is KH-560 coupling agent;

[0149] The particle size of fumed silica is 7 to 40 nm;

[0150] The material B is the curing agent of Example 2;

[0151] The ratio of the epoxy equivalent of the material A to the active hydrogen equivalent of the material B excluding the hydroxymethyl urea compound is 1:1;

[0152] The preparation method of the two-component coating comprises the following steps:

[0153] (1) Pour the Olin DER-440 epoxy resin and Huntsman EPN-1180 epoxy resin preheated to 60° C. into a double planetary high-speed disperser, add trimethylolpropane triglycidyl ether and KH-560 coupling agent, mix at 800 rpm for 5 min, continue to add fumed silica, mix at 200 rpm for 5 min, continue to add glass flakes and glass powder, mix at 900 rpm for 25 min, and then vacuum degas at 0.01 MPa for 20 min to obtain material A with an epoxy equivalent of 304.6 g / mol;

[0154] (2) Mix material A and material B in a mass ratio of 3.6:1 to obtain a two-component coating.

[0155] Comparative Example 1 (without addition of hydroxymethyl urea compound)

[0156] The curing agent is prepared from the following raw materials in parts by weight:

[0157] 84 parts of phenalkamine curing agent,

[0158] 15 parts of diethylenetriamine,

[0159] and 1 part of fumed silica;

[0160] The particle size of fumed silica is 7 to 40 nm;

[0161] The preparation method of the curing agent is as follows: weigh a phenalkamine curing agent, diethylenetriamine and fumed silica, and mix them at 1000 rpm for 30 minutes to obtain a curing agent with an active hydrogen equivalent of 76.3 g / mol.

[0162] Comparative application example 1

[0163] The raw materials of two-component coatings are composed of material A and material B;

[0164] The ratio of the epoxy equivalent of material A to the active hydrogen equivalent of material B is 1:1;

[0165] The raw materials of material A are the same as those in application example 1;

[0166] The material B is the curing agent of Comparative Example 1;

[0167] The preparation method of the two-component coating comprises the following steps:

[0168] (1) Same as Application Example 1;

[0169] (2) Mix material A and material B in a mass ratio of 4.0:1 to obtain a two-component coating.

[0170] test:

[0171] 1) Organic acid resistance test (with 99wt% glacial acetic acid as medium):

[0172] The two-component coatings prepared in Application Example 1, Application Example 2 and Comparative Application Example were cast into cylinders with a diameter of 12.7 mm and a height of 2.5 mm, cured at room temperature for 7 days, and then immersed in 99 wt % glacial acetic acid at room temperature. The weight change was tested at intervals. The results are shown in Tables 1 and Figure 1 As shown, Figure 1 The weight loss curves of the cylinders prepared with the two-component coatings of Application Examples 1-2 and Comparative Application Example 1 when immersing in 99wt% glacial acetic acid.

[0173] Table 1 Weight loss data of cylinders prepared by two-component coatings of Application Examples 1-2 and Comparative Application Example 1 when immersed in 99wt% glacial acetic acid

[0174]

[0175] From Table 1 and Figure 1 It can be seen that the coating provided by the present invention can effectively resist organic acids and has excellent long-term effects; Application Example 1 has better resistance to organic acids than Application Example 2; Compared with Application Example 1, omitting the hydroxymethyl urea compound will greatly reduce the resistance to organic acids of the coating.

[0176] 2) Inorganic acid resistance test: The two-component coating of Application Example 1 was cast into a cylinder with a diameter of 12.7 mm and a height of 2.5 mm, and then immersed in a specified inorganic acid at room temperature for 7 days (168 h) and observed for changes in its surface and weight as shown in Table 2 and Figures 2 to 5 As shown, Figure 2 This is a macroscopic image of a cylinder prepared by using the two-component coating of Application Example 1 (i.e., a macroscopic image before immersion); Figure 3 This is a macroscopic image of a cylinder prepared by the two-component coating of Application Example 1 and immersed in 37 wt % hydrochloric acid for 7 days; Figure 4 This is a macroscopic image of a cylinder prepared by the two-component coating of Application Example 1 and immersed in 98wt% sulfuric acid for 7 days; Figure 5 This is a macroscopic image of a cylinder prepared with the two-component coating of Application Example 1 and immersed in 40 wt % hydrofluoric acid for 7 days.

[0177] Table 2 Weight loss data of the cylinder prepared by the two-component coating of Application Example 1 when immersed in inorganic acid

[0178]

[0179] From Table 2 and Figures 2 to 5 It can be seen that the two-component coating of the present invention has a wide range of resistance to inorganic acids.

[0180] It can be seen from the above examples and comparative examples that the two-component coating prepared with the curing agent provided by the present invention has excellent acid corrosion resistance.

[0181] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A curing agent is prepared from the following raw materials in parts by weight: 60-85 parts of phenalkamine curing agent, 5 to 20 parts of diethylenetriamine, and 5 to 20 parts of hydroxymethyl urea compounds.

2. The curing agent according to claim 1, characterized in that The methylol urea compound includes at least one of monomethylol urea, dimethylol urea and trimethylol urea.

3. The curing agent according to claim 1, characterized in that The method for preparing the phenalkamine curing agent comprises: mixing long-chain phenol, paraformaldehyde, polyamine and solvent, and performing polymerization reaction to obtain the phenalkamine curing agent; The chain length of the long-chain phenol is at least one of C7 to C15.

4. The curing agent according to claim 3, characterized in that The long-chain phenol includes at least one of cardanol, heptylphenol, octylphenol, nonylphenol and decylphenol.

5. A two-component coating, the raw materials include material A and material B; The material A is prepared from the following raw materials in parts by weight: 30-45 parts of multifunctional epoxy resin, Epoxy reactive diluent 5-15 parts, Barrier filler 20-60 parts, 10-30 parts of glass powder, and 0.3 to 1 part of coupling agent; The material B is the curing agent according to any one of claims 1 to 4; The ratio of the epoxy equivalent of the material A to the active hydrogen equivalent of the material B excluding the hydroxymethyl urea compound is (0.9-1.1): (0.9-1.1).

6. The two-component coating according to claim 5, characterized in that: The multifunctional epoxy resin includes at least one of phenolic epoxy resin, resorcinol formaldehyde epoxy resin, tetraphenol ethane tetraglycidyl ether and tetraglycidyl diaminodiphenylmethane.

7. The two-component coating according to claim 5, characterized in that: The epoxy reactive diluent includes at least one of aliphatic glycidyl ether and aromatic glycidyl ether.

8. The two-component coating according to claim 5, characterized in that: The barrier filler includes at least one of glass flake powder, lamellar boron nitride and mica powder.

9. A coating, wherein the coating is composed of the two-component coating according to any one of claims 5 to 8.

10. Use of the two-component coating according to any one of claims 5 to 8 or the coating according to claim 9 in acid corrosion resistance.

Citation Information

Patent Citations

  • Composite alkaline phenolic resin curing agent, preparation method and application

    CN104212123A

  • Compound type epoxy curing agent applied to heavy anti-corrosion coating and preparation method

    CN106995527A

  • Underfill adhesive for semiconductor packaging and semiconductor packaging structure with flip chip

    CN113403013A

  • Additive for thermocurable epoxy resin compositions

    DE3919431A1

  • Novel phenolic resin composition

    JP1987241953A

Cited By

  • Multi-chemical-medium-resistant cross-linked network coating and preparation method thereof

    CN121450189A